Republicanism and postmodernism in new social movements: An approach to the indignados movement - Abellán López, María Ángeles (2015)
This paper explores some theoretical links between contemporary republicanism and social movements, with a postmodern approach, in a search for greater participation, democratic regeneration and political innovation through the centrality of public spaces as a political locus. Using the indignados movement, the main political demands aimed at deepening democracy and assuming republican civic values will be addressed in this paper.